Construction and Analysis of Urban Motor Vehicle Drivers' Traffic Literacy Evaluation Model Based on Zhengzhou City's Survey Data. (16th February 2022) - Shengyang, Liu; Yanrong, Wang; Kang, Tian; Fangzheng, Hu
Abstract : This paper summarizes the relevant literature through the content analysis method and combines expert advice. The company built a four-level indicator including traffic knowledge and skills, and 13 pilot-level traffic literacy evaluation indicators system including traffic rules and mechanical common sense. The Analytic Hierarchy Process (AHP) analysis method is used to determine the weight of each indicator of urban driver traffic literacy evaluation, and conduct pilot survey and evaluation of motor vehicle drivers in Zhengzhou. The results show that the evaluation value of motor vehicle driver traffic literacy in Zhengzhou is 72.07, including a traffic knowledge score of 77.09, traffic awareness score of 73.95, traffic skill score of 78.12, and traffic behavior score of up to 84.3. It shows that the respondents have relatively more active and responsible traffic behaviors and have a certain degree of understanding of traffic skills and traffic knowledge. However, they are relatively low in traffic awareness.